2004
DOI: 10.1063/1.1652232
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial GaN1−yAsy layers with high As content grown by metalorganic vapor phase epitaxy and their band gap energy

Abstract: GaN 1ϪyAs y epitaxial alloy samples with ͓N͔ӷ͓As͔ were grown by metalorganic vapor phase epitaxy. The range of As content achieved, up to yϭ0.067, greatly extends the range of achievable As levels to values that are well within the miscibility gap of the GaN-GaAs system. The single-phase epitaxial nature of the alloy samples was confirmed by x-ray diffraction. The As-content dependence of the band gap was determined by optical absorption measurements. A highly-bowed bandgap was observed as a function of the As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 8 publications
3
33
1
Order By: Relevance
“…It was found that GaN doped with As at low, impurity like levels shows a characteristic blue emission at room temperature. At higher As doping levels an abrupt decrease in the band gap of resulting GaN 1-x As x alloys was observed [9,10,11,12]. Fig.…”
Section: Dilute Alloysmentioning
confidence: 95%
See 2 more Smart Citations
“…It was found that GaN doped with As at low, impurity like levels shows a characteristic blue emission at room temperature. At higher As doping levels an abrupt decrease in the band gap of resulting GaN 1-x As x alloys was observed [9,10,11,12]. Fig.…”
Section: Dilute Alloysmentioning
confidence: 95%
“…For both techniques, it is difficult to obtain a high concentration of As in the alloy before phase separation occurs. The 6 highest reported As content in MOVPE grown layers is x~0.067 [10,11,12] [21,22,23]. The atomic diffusion length in these non-equilibrium processes is long enough to form crystalline lattices with uniform compositions, but short enough to avoid equilibrium phase segregation.…”
Section: Low Temperature Molecular Beam Epitaxial Growth Of Ga-n-asmentioning
confidence: 99%
See 1 more Smart Citation
“…The smaller size of N allows its solubility in GaAs and extensive research has been reported on such alloys [3][4][5][6][7][8]. In comparison, owing to the larger size of As and consequent difficulty in the incorporation of As in GaN, very limited work has been reported on N-rich side of GaAs x N 1−x alloys, which have been mostly prepared by MOCVD and MBE [9,10]. N-rich GaAs x N 1−x alloys are important materials for extending the wavelength range of GaNbased blue light emitting devices towards the red/infrared region.…”
Section: Introductionmentioning
confidence: 99%
“…5,[19][20][21][22][23][24][25][26][27][28] Li and co-workers first succeeded in incorporating As into thin film GaN through metal-organic chemical vapor deposition (MOCVD), and the redshift of band gap energy of the dilute-As GaNAs alloy was observed in the photoluminescence study. 5 Further studies have also shown successful incorporation of As-content up to 7% into GaN material through MOCVD, 20 and synthesis of GaNAs alloy in full composition range through molecular beam epitaxy (MBE) was recently reported. 21 Recent experimental work by Yu et al reported that the band gap of dilute-As GaNAs alloy reaches 2.3 eV ± 0.5 eV at roughly 6%-As impurities incorporation.…”
Section: Introductionmentioning
confidence: 99%